Haiti : Request for Extension of the Arrangement Under the Poverty Reduction and Growth Facility; Staff Report. (IMF Staff Country Reports; Country Report ;, 2011)
According to the fifth review of the Poverty Reduction and Growth Facility (PRGF) arrangement, the Haitian authorities remain committed to macroeconomic stability under the program. On completion of the fifth review of the PRGF, they requested a new three-year Extended Credit Facility (ECF) arrangement to help sustain economic growth and to preserve macroeconomic stability. The IMF Board approved a three-year arrangement for Haiti under the PRGF. This will help ensure that endorsement of policy measures to preserve macroeconomic stability and sustain growth in Haiti can be undertaken before the current PRGF expires.